Comparison of the conceive-design-implement-operate model and lecture-based learning in teaching the “healthcare-associated infections” course - Chen, Yu; Zhang, Rui; Zhou, Zhenke; Hong, Min; Huang, Zheng; Wen, Heling; Peng, Lei (Frontiers in Medicine, 2025)
BackgroundHealthcare-associated infections (HAI) are infections acquired by patients during treatment in various healthcare institutions. These infections significantly increase morbidity, mortality, and healthcare costs. Enhancing HAI education for nurses can improve patient safety and medical quality.AimThe study aimed to assess the effectiveness of the new conceive-design-implement-operate (CDIO) teaching model on nursing students’ HAI learning outcomes and compare it with the traditional LBL model, providing valuable insights for future HAI education in nursing.MethodsA total of 110 nursing students were randomly assigned to one of two groups for HAI training during the 2022–2023 academic year: a group that engaged in the CDIO model and another that received traditional lecture-based learning (LBL). The effectiveness of these pedagogical approaches was evaluated by comparing pre-and post-training test scores, and we used the Course Experience Questionnaire (CEQ) to collect students’ feedback on the course and teaching.ResultsCompared to traditional LBL method, the CDIO model significantly improved the overall scores and practical application scores of nursing students in the HAI course, with these advantages still retained after 24 weeks. Additionally, preliminary results show that students in the CDIO model scored higher on CEQ categories such as good teaching, clear goals and standards, appropriate assessment, generic skills, and independence, but they also reported an increased workload.ConclusionOur research is the first to apply the CDIO framework to nursing education in HAI courses, enhancing nursing students’ practical application skills, particularly in the sustained retention in this area. Our study indicates that the CDIO teaching model has significant advantages in enhancing course experience and teaching effectiveness.